HOPE AND LOVE IN THE POEM ILĀ BAIRŪT AL-UNṠĀ MA‘A AL-I‘TIŻĀR BY NIZĀR QABBĀNĪ: A STUDY OF ROLAND BARTHES' SEMIOTICS - Muhammad Faishol Al Hamimy (Arabic Literature Department, 2025)
Every literary work reflects the author’s hopes and goals, conveyed through a particular point of view intended to influence the reader, resulting in various interpretations. This study aims to explore the meanings of love and hope in the poem Ilā Bairūt al-Unṡā Ma‘ al-I‘tiżār by Nizār Qabbānī. The focus is: 1) What are the denotative, connotative, and mythical meanings in the poem? 2) How are the poet’s love and hope represented? This research uses a qualitative descriptive method with Roland Barthes’ semiotic approach. Data collection techniques include literature review and internet research. The results show: 1) Thirty-five denotative words and sentences were identified, each carrying connotative meanings; the mythical meaning emphasizes nationalism, patriotism, unity, and responsibility to prevent national destruction. 2) The representation of love includes: attention, shown through admiration for Lebanon’s natural and cultural beauty; responsibility, through awareness of Lebanon’s condition and rejection of its destruction; respect, by valuing Lebanon’s charm and contributions; and understanding, recognizing Beirut as a unique and irreplaceable city that needs love and care. The poet hopes readers will acknowledge Lebanon’s role and foster awareness, responsibility, and unity to improve the nation.